2019
DOI: 10.1155/2019/5769752
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity of DON on GPx1-Overexpressed or Knockdown Porcine Splenic Lymphocytes In Vitro and Protective Effects of Sodium Selenite

Abstract: Deoxynivalenol (DON) is a common contaminant of grain worldwide and is often detected in the human diet and animal feed. Selenium is an essential trace element in animals. It has many biological functions. The role of selenium in the body is mainly orchestrated by selenoprotein. Glutathione peroxidase (GPx) also exists widely in the body and has attracted much attention due to its high antioxidant capacity. In order to explore the effect of the GPx1 gene on toxicity of DON, in this study, we overexpressed or k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…Since, Se is considered an essential part of different antioxidant enzymes, such as GPx and thioredoxin , it plays an important role in the antioxidant defense mechanisms in the body. An in vitro study showed that sodium selenite could regulate the antioxidant capacity, apoptosis rate, and expression of DNA methylation-related genes in pig splenic lymphocytes (Ren et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Since, Se is considered an essential part of different antioxidant enzymes, such as GPx and thioredoxin , it plays an important role in the antioxidant defense mechanisms in the body. An in vitro study showed that sodium selenite could regulate the antioxidant capacity, apoptosis rate, and expression of DNA methylation-related genes in pig splenic lymphocytes (Ren et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…The main aim of this review was to systemize and sum up the available studies covering the effects of antioxidant defense gene overexpression on cell resistance to oxidative stress. We analyzed 166 such works [ 20 , 51 , 56 , 58 , 62 , 65 , 66 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 , 99 , 100 , 101 , 102 , 103 , 104 , 105 , 106 , 107 , 108 , 109 , 110 , 111 , 112 , 113 , 114 ,…”
Section: Effects Of Antioxidant Defense Gene Overexpression On Stress...mentioning
confidence: 99%
“…Increased resistance: UVB [96], deoxynivalenol [97], cisplatin [99,103,105], X-ray [100], doxorubicin [106], H 2 O 2 , GSH high concentration [107] Decreased resistance: cisplatin [103], gemcitabine [104] in vivo Increased resistance: ischemia-reperfusion injury [98], cocaine [101], microcystin-leucine-arginine [102] GPX2 in vitro Increased resistance: cisplatin [108] GPX3 in vitro Increased resistance: ascorbate [109], cisplatin [110], NAPQI [111] GPX4 in vitro…”
Section: Cat In Vitromentioning
confidence: 99%
“…It was found that 10 mM DON increased the percentage of 5-methylcytosine in DNA from 4.5-9% in Caco-2 cells [59]. However, another study reported that DON at 3 mg/kg decreased the expression of methyltransferases and upregulated methyl-CpGbinding domain 2 (MBD2) expression in porcine splenic lymphocytes [60]. Abnormal changes in DNA methylation are common in tumorigenesis [61].…”
Section: Donmentioning
confidence: 99%